Caracterização, pré-tratamentos, hidrólises enzimáticas e fermentação alcoólica de sorgo biomassa [Sorghum bicolor (L.) Moench] - Santos, Beatriz Vieira dos (2019)
Sorghum biomass (SB) is a kind of sorghum sensitive to photoperiod with high productivity in biomass, and higher content in polysaccharides (cellulose and hemicelluloses), becoming a promising crop for application in the production of second generation ethanol (2G ethanol) . In this context, in the first stage of this study, the efficiency of an enzymatic extract produced by solid state fermentation (SSF) was evaluated using a consortium between the fungi Aspergillus fumigatus SCBM6 and A. niger SCBM1 in the hydrolysis of crude SB and after the removal of extractives (SE). After SSF, with respect to hemicellulase production, maximum peaks of xylanase (375 U g -1) on day 4 and β-xylosidase (150 U g -1) were obtained on 2nd day of co-cultivation. For cellulases, peaks of production were observed on the 1st day of fermentation (80 U g-1) for β-glycosidase and on 6 day (80 U g-1) for endoglucanase (CMCase) and cellulase on filter paper (FPase) (4 U g-1). After the enzymatic hydrolysis using the extract produced by the fungal consortium, the xylose and glucose release increased in SE about 10x (2.5 gL-1 after 12 hours), indicating that the withdrawal of extractives positively influenced hydrolysis efficiency and yields in fermentable sugars. The extraction of the extractives also represented a positive factor for the decrease of the formation of inhibitor compounds of alcoholic fermentation, such as formic acid. In the second stage, the ethanol yield was evaluated from hydrolysates of sorghum biomass previously submitted to three different chemical pre-treatments (PTs): sodium hydroxide (NaOH-1 and 2%), hydrochloric acid (HCl = 0.34 and 1.5%) and alkaline hydrogen peroxide (H2O2-5 and 7.36%) using the commercial enzymes Celluclast 1.5 L (10FPU) and Novozym 188 (30CBU) in the hydrolysis and the yeast Pichia stipitis in the alcoholic fermentation. Among the evaluated PTs, PT with 7.36% H2O2 was the most efficient in lignin removal and preservation of the polysaccharide fraction. After the hydrolysis, it was observed that the xylose concentrations remained practically unchanged in the hydrolysates of SB ¨in natura¨ and SE (without extractives). However, in the pre-treated sorghum hydrolysates, a large increase in xylose concentration was observed, especially in the hydrolysates of pretreated HCl and H2O2 sorghum. This increase was even more significant in sorghum hydrolysates pretreated with 0.34% HCl and 5% H2O2. Regarding glucose, the sorghum pretreated with H2O2 favored the highest release of this monosaccharide after enzymatic hydrolysis. In addition, all hydrolysates showed low concentrations of inhibitors. After hydrolysis, the highest ethanol yields were obtained in fermentations carried out with the hydrolysates of SB pretreated with HCl (0.34 and 1.5%), obtaining 3.84 and 3, 61g.L-1 ethanol, corresponding respectively to 16.15 and 14.62% yield. The results indicated that sorghum biomass presents potential for use as raw material in the production of ethanol, opening prospects for additional studies in order to optimize the process and obtain more expressive yields in ethanol.